Boosting Electrical Response toward Trace Volatile Organic Compounds Molecules via Pulsed Temperature Modulation of Pt Anchored WO3 Chemiresistor. Issue 10 (26th August 2022) - Dai, Tiantian; Yan, Zhi; Li, Meng; Han, Yulei; Deng, Zanhong; Wang, Shimao; Wang, Ruyang; Xu, Xiaohong; Shi, Lei; Tong, Wei; Bao, Jun; Qiao, Zhenhua; et al.
Abstract: Insufficient limit of detection (LoD) toward volatile organic compounds (VOCs) hinders the promising applications of metal oxide chemiresistors in emerging air quality monitoring and/or breath analysis. There is an inherent limitation of widely adopted strategies of creating sensitive chemiresistors then operating at the optimized temperature via a continuous heating (CH) mode. Herein, a strategy combining Pt single atoms anchoring (chemical sensitization) with pulsed temperature modulation (PTM, physical sensitization) is proposed. Apart from generating abundant surface asymmetric oxygen vacancy (Pt‐VO ‐W) active sites at pulsed high temperature (HT) stage, inward diffusion of trace target VOCs across the sensing layer at pulsed low temperature stage (driven by PTM induced concentration gradient), can greatly enhance the charge interaction probability between the generated surface active species and the surrounding VOCs, and thus offers a novel avenue on addressing the bottleneck issue of low LoD by PTM. Triggered by HT of 300 °C, the responses of Pt anchored WO3 chemiresistor to 1 ppm trimethylamine (TMA) and xylene can be drastically boosted from 1.9 (CH) to 6541.5 (PTM) and 1.5 (CH) to 1001.1 (PTM), respectively. And ultra‐low theoretic LoD of 0.78 ppt (TMA) and 0.18 ppt (xylene) are successfully achieved, respectively. Abstract : The introduction of surface asymmetric oxygen vacancy (Pt‐VO ‐W) defects by Pt single atoms anchoring (chemical sensitization), and inward diffusion of trace volatile organic compounds (VOCs) within the sensing layer induced by pulsed temperature modulation (physical sensitization) plays an important role in boosting the electrical response of oxide chemiresistors toward the trace tested VOCs.